General Protocol to Obtain D‐Glucosamine from Biomass Residues: Shrimp Shells, Cicada Sloughs and Cockroaches. Issue 11 (24th August 2018) - Bertuzzi, Diego L.; Becher, Tiago B.; Capreti, Naylil M. R.; Amorim, Julio; Jurberg, Igor D.; Megiatto, Jackson D.; Ornelas, Catia
Abstract: A general protocol is developed to obtain D‐glucosamine from three widely available biomass residues: shrimp shells, cicada sloughs, and cockroaches. The protocol includes three steps: (1) demineralization, (2) deproteinization, and (3) chitin hydrolysis. This simple, general protocol opens the door to obtain an invaluable nitrogen‐containing compound from three biomass residues, and it can potentially be applied to other chitin sources. White needle‐like crystals of pure D‐glucosamine are obtained in all cases upon purification by crystallization. Characterization data (NMR, IR, and mass spectrometry) of D‐glucosamine obtained from the three chitin sources are similar and confirm its high purity. NMR investigation demonstrates that D‐glucosamine is obtained mainly as the α‐anomer, which undergoes mutarotation in aqueous solution achieving equilibrium after 440 min, in which the anomeric glucosamine distribution is 60% α‐anomer and 40% β‐anomer. Abstract : The valuable nitrogen‐containing compound D‐glucosamine is easily obtained from biomass residues such as shrimp shells, cicada sloughs, and cockroaches, utilizing a simple, general protocol. The mutarotation process of D‐glucosamine obtained is investigated by 1 H NMR, showing that the anomeric equilibrium in aqueous solution is achieved after 440 min.